Pemberdayaan Remaja Dalam Mencegah Pernikahan Dini Dan Stunting - Marcelina, Sheilla Tania; Yudianti, Ika; Sondakh, Jenny JS; Astutik, Heny; Tarsikah (DHARMA BAKTI, 2021)
Adolescence is a crisis stage, is a transition from childhood to adulthood. From adolescence, some health-related health problems are early marriage and stunting. Based on data from the Bumiaji Health Center, the number of early marriages in the last six months of 2020 in Gunungsari village was classifying as the highest. The highest stunting rate is in Gunungsari Village within a percentage of 20.9%, and the data for toddlers with stunting is 87 children in August 2020 and 85 children in October 2020. Youth empowerment carrying out by increasing knowledge topics about Marriage Age Maturation, reproductive health education, stunting and its relationship to early marriage. Knowledge improvement evaluating from the pretest and post-test. Assessment of this activity by observing positive activities carrying out by teenagers. The implementation of community service activities went well, and the community was very active in participating in the activities. This enthusiasm is reflected by the youth cadres to ask questions and discuss, and the post-test results show an increase. The final result can evaluate from the existence of a Posyandu Remaja. This implementation once a month by youth cadres to all youth in Gunungsari Village. Adolescents are the hope to continue their noble values and potential. The impact of implementing youth empowerment is optimizing adolescent reproductive health in a group of healthy friends. The youth as health workers are also representatives of cadres who understand adolescent reproductive health and can become sources of information for their peer group.